Вплив структури нестаціонарного потоку на теплоообмін у перехідному пограничному шарі - Супрун, Т. Т. (Energy and Automation, 2017)
INFLUENCE OF UNSTEADY FLOW STRUCTURE ON НЕAT TRANSFER IN TRASITIONAL BOUNDARY LAYER T. Suprun It is known that the laminar-turbulent transition which is widely spread in flow passages of heat power equipment, including turbomachinery, occurs under complex external conditions (free-stream turbulence, separation, velocity instability, etc.). The origin of bypass laminar-turbulent transition at elevated free-stream turbulence has been investigated in details in our previous works. According to these works, bypass transition is preceded by the so-called pseudolaminar boundary layer and followed by a quasiturbulent boundary layer, which exhibit a number of specific features, first of all the increase of transport coefficients. Unsteady flows with velocity instability after moving obstructions are also widely spread in various technical applications. The typical example is flow in turbomachines after working blades. Under influence of both elevated free-stream turbulence and periodic velocity instability wake-induced transition with specific features arises. The modelling of the periodic velocity instability is often realized by means of “squirrel cage”. Namely influence of such velocity unsteadiness on wake-induced transition is the object of given presentation. The experiments were carried out at velocity 9 m/s in a wind tunnel T-5 of IET NASU with working section 120x120x800 mm. A heated flat plate was mounted in working section asymmetrically at =90 mm from top wall. In order to eliminate separation at the leading edge of the plate the interceptor at a height of 60 mm was installed on the top wall at the end of working section. For generating periodic unsteady wakes “squirrel cage” (D=70 mm) with 6 cylinders (d=3 mm) and frequency 5 Hz was used. The parameters of the internal structure of the boundary layer and the external flow were measured by DISA-55M system. The results of measurements of mean in time velocities and total longitudinal fluctuations at different distances from the source of disturbances are presented below. The distributions of mean in time velocities in the chosen sections (x=50-600 mm) at y=5-85 mm demonstrate the presence of as the shearless core broading downflow as the zone of shear flow on the periphery of “squirrel cage”. The common tendency is weakening of velocity defect with x growth. The direction of rotation of “squirrel cage” does not influence on the velocity distribution. The distributions of total fluctuations () including turbulent () and nonstationary () components differ by peaks, amplitude of which decreases downflow. Mechanism of peaks origin is connected with interaction of wakes after rotating obstructions (cylinders) what causes the growth of energy of disturbances in points of intersections of wakes. For using the characteristics of shear external flow after moving “squirrel cage” in further calculations, its replacement by shearless equivalent was made. For this purpose in the every cross section the distributions of velocity and fluctuations were averaged in the range of which corresponded the width of wakes spreading. The decay law of average total fluctuations was similar to the one after traditional still grids widely used for generation of turbulence in aerodynamic tubes. The values of total fluctuations changed from 15 to 4.3% at x=50 and 600 mm respectively. On the basis of experimental investigations the methodic of division of turbulent and nonstationary modes in unsteady flows is proposed. For dividing turbulent and nonstationary components the additional measurement were conducted after still “squirrel cage”. The method of dividing was based on two following assumptions: the rotation does not substantially influence on turbulent component and the energies of disturbances of different nature are not correlated, i.e. . In this case nonstationary component is calculated as. The results of experimental investigations shown that the fluctuations of turbulent component measured after still “squirrel cage” changed slower than calculated fluctuations of nonstationary component. Immediately near the “squirrel cage” the role of nonstationarity was dominant, however downflow turbulent component became prevailing. This fact must be taken into account for development of modern calculating methods of complex transport processes. For estimating the influence of the wakes on the characteristics of the thermal transition the results of heat transfer investigation without “squirrel cage” with natural transition at =0.2-0.4% were used. In this case the region of natural transition is Rexst- Rexend =2·105-4·105. For comparison the results of experiments with other moving obstructions organised by still and hesitating cylinder were also used. In case of steady wake generation after still cylinder the distribution of local heat transfer coefficients along the plate is changed: the start of wake-induced transition is shifted upstream relatively natural transition which occurred without wakes and heat transfer in the pre-transition boundary layer is increased. In the presence of hesitating cylinder the distribution became smoother than in previous case but remained non-monotone. After still and rotating “squirrel cage” the distribution became monotone and the existence of wake laminar-turbulent transition of upper type is confirmed. Intensification of heat transfer in the pre-transition boundary layer in cases of steady and periodic wakes is estimated and was correspondingly 1.4-1.67 and 1.49-1.78 at Rex==2·104-4·104 relatively laminar boundary layer. The region of wake-induced transition is fixed: Rexst- Rexend =5.2·104-1.92·105 and 4.5·104-1.55·105 respectively. Obtained results of experimental study of wake-induced transition should provide test cases for improving the heat transfer modeling and enhancing the accuracy of thermal load prediction for various technical applications, including turbomachinery.